Aksi Sosial Katolik, Oposisi terhadap Penguasa, dan Sikap Nasionalis Katolik di Jawa pada Awal Abad ke-20 - Amos Sukamto (Reformed Center for Religion and Society, 2026)
This article focuses on Catholic involvement in national upheavals, both through education, politics, and the struggle for independence. Using historical methods, several findings are obtained. The development of social action and nationalist attitudes among Javanese Catholics resulted from a dialectical interaction between global inspiration and local dynamics. The experiences of European Catholics' socio-political struggles and papal encyclicals served as sources of inspiration, which were then diffused to the Dutch East Indies through missionaries. This diffusion process was effective because it met local needs, namely a sense of indigenous emancipation and national awakening. In the local context, the Van Lith educational institution produced a Javanese Catholic elite. Graduates became agents of modernization, connecting universal Catholic values ​​with national aspirations, while simultaneously forming a collective identity rooted in Javanese culture. This identity became the basis of solidarity that fostered the emergence of Javanese Catholic social and political organizations. The Javanese Catholic political movement was an effort to build counter-hegemony against Dutch colonial domination, manifested in a critical stance against government policies and its support for local people.